Fibrinogen and Albumin Score Changes during Preoperative Treatment Can Predict Prognosis in Patients with Locally Advanced Rectal Cancer - Meng-Jun Tang; Shu-Bo Ding; Wang-Yuan Hu (Gastroenterology Research and Practice)
Background. Fibrinogen (Fib) and albumin (Alb) levels are indicators of systemic inflammatory responses. Elevated Fib and decreased Alb levels are considered negative prognostic factors in different types of cancer. Here, we explored the prognostic value of changes in pre- and post- neoadjuvant chemoradiotherapy (NCRT) plasma fibrinogen and serum albumin (FA) scores in patients with locally advanced rectal cancer (LARC). Methods. A total of 106 patients with LARC who underwent NCRT followed by surgical resection at Jinhua Municipal Central Hospital between 2011 and 2015 were analyzed. In addition, plasma Fib and serum Alb levels before and after NCRT were collected. FA scores were calculated based on the Fib and Alb levels dichotomized by clinical reference values. Patients were classified into two groups based on the changes in FA scores during NCRT: in group A, FA scores decreased or remained unchanged (n=84), and in group B, FA scores increased (n=22). Changes in FA scores were compared with patient outcomes. Results. Increased FA scores were associated with worse disease-free survival (DFS) and overall survival (OS) in patients with LARC. The occurrence of systemic failure was higher in group B than in group A (40.9% vs. 19%, P=0.032). In multivariate analysis, changes in FA scores, pretreatment carcinoembryonic antigen (CEA) levels, and pathologic differentiation were independent prognostic parameters for DFS and changes in FA scores and pretreatment CEA levels were independent prognostic parameters for OS. Conclusions. Increased FA score after NCRT was an independent negative prognostic factor for DFS and OS in patients with NCRT-treated LARC.